2010
DOI: 10.7326/0003-4819-153-4-201008170-00002
|View full text |Cite
|
Sign up to set email alerts
|

Liability Claims and Costs Before and After Implementation of a Medical Error Disclosure Program

Abstract: Blue Cross Blue Shield of Michigan Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
190
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(198 citation statements)
references
References 24 publications
3
190
0
5
Order By: Relevance
“…Both limited-reimbursement and full-compensation model programs have reported that malpractice claims decreased following program implementation. 5,6 Attorney consultations may actually prove helpful in facilitating early settlement, if attorneys confirm that offers are fair and reasonable, or at least more attractive than patients' prospects in lawsuits. Some institutions currently operating disclosure-and-resolution programs refer patients-particularly those who have been seriously injured or appear distrustful-to reputable plaintiff's attorneys who provide good-quality representation and have demonstrated openness toward early settlement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both limited-reimbursement and full-compensation model programs have reported that malpractice claims decreased following program implementation. 5,6 Attorney consultations may actually prove helpful in facilitating early settlement, if attorneys confirm that offers are fair and reasonable, or at least more attractive than patients' prospects in lawsuits. Some institutions currently operating disclosure-and-resolution programs refer patients-particularly those who have been seriously injured or appear distrustful-to reputable plaintiff's attorneys who provide good-quality representation and have demonstrated openness toward early settlement.…”
Section: Discussionmentioning
confidence: 99%
“…3 Early disclosure-and-resolution adopters report promising results. [4][5][6][7] However, few publicly available data exist concerning the programs' effectiveness. Even less is known about what accounts for their reported success-and to what extent patients' favorable responses to the disclosure-and-resolution approach are attributable to effective disclosure or apology practices versus compensation offers.…”
mentioning
confidence: 99%
“…The adoption of this program has decreased liability claims, patient lawsuits, resolution time, and associated costs. 3 In response to this study, we believe that the cultures of medicine and health care should be even more accepting of physician practices of openly admitting mistakes and apologizing.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the programme found a decrease in new legal claims, number of lawsuits per month, time to claim resolution, and costs after implementation of the program of disclosure with offer of compensation. This approach did not increase legal claims and costs even in the notoriously litigious United States (Kachalia et al 2010 ); in fact some decline in litigation was reported in Michigan generally through the latter part of the study period. Several New York hospitals have now implemented similar 'communication and resolution programmes'.…”
Section: Box 72 Medically Induced Trauma Support Services (Mitss)mentioning
confidence: 99%